MARJINALISASI (PUBLIK) AKTIVIS DALAM LITERATUR PUBLIC RELATIONS - Kusumaningtyas, Nurhidayati (Informasi, 2015)
AbstractActivism can involve an individual or a collection of a few people. The practice of activism is often perceived as negative and destructive actions. In the literature of public relations, we will discover how the activist group pressure group categorized into the "source of trouble" and must be addressed by public relations practitioners. This perspective led to a bias that leads to marginalization of "activist public" in public relations literature. Marginalization process lasts through two methods: (1) the provision of which tend negative stigma, (2) the dominance of the paradigm of "corporate centric" in the literature of public relations. This article presents an alternative paradigm of the postmodern paradigm in view of the role and functions of the public activists.AbstrakAktivisme bisa melibatkan seorang individu ataupun kumpulan beberapa orang. Praktek aktivisme seringkali dipersepsikan sebagai tindakan yang negatif dan destruktif. Dalam literatur public relation, kita akan menemukan bagaimana kelompok aktivis dikategorikan kedalam kelompok penekan yang menjadi "sumber masalah" dan harus diatasi oleh praktisi public relations. Perspektif ini memunculkan bias yang mengarah pada marjinaliasi "publik aktivis" dalam literature public relation. Proses marjinalisasi berlangsung melalui dua cara: (1) pemberian stigma yang bertendensi negative, (2) adanya dominasi paradigma "corporate centric" dalam literatur public relation. Artikel ini menyajikan alternatif paradigma yakni paradigma postmodern dalam melihat peran dan fungsi publik aktivis.Keywords: Public Activist, Corporate Centric, Marginalization.